Cote D'Ivoire : Seventh Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Cote d'Ivoire's Seventh Review Under the Extended Credit Facility (ECF) Arrangement and Request for Modification of Performance Criteria (PCs). Performance under the IMF-supported program continued to be strong. Over 2012-14, the growth in real GDP per capita has reached 20 percent. All PCs and all but one indicative targets for end-2014 were met. Significant progress has been made toward improving the business climate and the tax administration, and some inroads have been made toward public bank restructuring. The IMF staff supports the authorities' request for completion of the seventh ECF review and for the modification of the PCs for end-June 2015 and indicative targets.